2023
DOI: 10.3389/fnut.2023.1116105
|View full text |Cite
|
Sign up to set email alerts
|

Current dietary intake of the Japanese population in reference to the planetary health diet-preliminary assessment

Abstract: IntroductionWe sought to assess the Japanese diet by examining the current dietary intake in Japan using the global reference diet from the EAT-Lancet Commission (Planetary Health Diet; PHD), from the perspective of protein intake in different age groups.MethodsAverage dietary intake by food group in the Japan National Health and Nutrition Survey 2019 (NHNS 2019) was converted to the PHD food groups, and the diet gap (DG) (%) of the global reference of the PHD was calculated by age group.ResultsAlthough the DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Nomura et al assessed the Japanese diet in relation to the global EAT-Lancet Commission's Planetary Health Diet (PHD), particularly focusing on protein intake across various age groups. Using data from the Japan National Health and Nutrition Survey 2019 (43), it was found that while most food group intakes exceeded the PHD's global reference across all age groups, only red meat intake significantly surpassed its upper limit, particularly in those in their 40s. Despite this, protein consumption in Japan remains within recommended limits.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…Nomura et al assessed the Japanese diet in relation to the global EAT-Lancet Commission's Planetary Health Diet (PHD), particularly focusing on protein intake across various age groups. Using data from the Japan National Health and Nutrition Survey 2019 (43), it was found that while most food group intakes exceeded the PHD's global reference across all age groups, only red meat intake significantly surpassed its upper limit, particularly in those in their 40s. Despite this, protein consumption in Japan remains within recommended limits.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…Tatsächlich könnte es zu einem Mangel an Kalzium, Vitamin B12, Eisen und Zink kommen, dem durch eine Modifikation der ursprünglich vorgeschlagenen PHD zu begegnen ist 13 . Die PHD stellt eine radikale Änderung aktuell vorherrschender Ernährungsgewohnheiten dar und ihre Umsetzung erfordert in den meisten Ländern eine Verminderung des Konsums von rotem Fleisch und Zucker um etwa 50 % und eine Steigerung der Aufnahme von Obst, Gemüse, Hülsenfrüchten und Nüssen um mehr als 100 % 14 15 16 17 .…”
Section: Lebensstilinterventionunclassified
“…Briefly, the ELHRD is framed to optimize both health and diet-related environmental impact and should be used at national/regional level to develop country specific healthy and sustainable diet, once adapted to the considered food context. The ELHRD prompted considerable scientific debate since its publication and has been compared to national Food-Based Dietary Guidelines (FBDGs) in USA ( Blackstone and Conrad, 2020 ) and Australia ( Hendrie et al, 2022 ), as well as current diets in India ( Sharma et al, 2020 ), Spain ( Cambeses-Franco et al, 2022 ), and Japan ( Nomura et al, 2023 ). Furthermore, several scores to evaluate adherence were elaborated and validated or used to assess the association with nutritional adequacy, indicators of environmental impact or risk of chronic diseases ( Ali et al, 2022 ; Cacau et al, 2021 , 2022 ; Cacau and Marchioni, 2022 ; Campirano et al, 2023 ; Colizzi et al, 2023 ; Frank et al, 2024 ; Hanley-Cook et al, 2021 ; Kesse-Guyot et al, 2021 ; Knuppel et al, 2019 ; López et al, 2023 ; Marchioni et al, 2022 ; Montejano Vallejo et al, 2022 ; Stubbendorff et al, 2022 ; Trijsburg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%